Creating lexical models: do foreign language learning techniques affect lexical organization in fluent bilinguals? - De la Garza, Bernardo (Kansas State University, 2012)
The use of different language learning methods for the purposes of acquiring foreign language vocabulary has long been explored but studies have often failed to take into account the potential effects on lexical processing. The current study examined the effectiveness of the Keyword, Context and Paired-Associate learning methods in acquiring foreign language vocabulary, but primarily focusing on the lexical and conceptual organization effects that each method may have on a foreign language learner. Three main theories/models (i.e., Word Association, Concept Mediated and Revised Asymmetrical Hierarchical) have been used to explain the organization of bilingual lexical, conceptual stores and connections between each store, but studies have not examined the addition of a third language (i.e., L3) and the potential connections created between new L3 and the two existing language stores. It was predicted that since low-proficiency bilinguals would create lexical models which heavily rely on translation equivalents, thus, the use of non-elaborative learning methods would assist in creating only lexical translation links, while more sophisticated elaborative methods would be successful in creating direct access to the conceptual meaning. The current study further explored the potential effects of language learning methods on comprehension ability, requiring the creation of situation models for comprehension. Finally, the present study explored the immediate and delayed effects of language learning methods on both vocabulary acquisition and comprehension ability. Results from the current study indicated that all learning methods were successful in creating and conceptual connections between the languages and the conceptual store, while Keyword learners had significantly better scores on certain trial types. Differences in terms in lexical and conceptual strength are suggested since differences in RTs and scores were found between some of the learning methods. Furthermore, in terms of comparisons across time, repeated testing learners attained better scores on all trial types in comparison to learners who were only tested at Time 2. Lastly, when assessing if lexical links could be created to a non-associated highly fluent second language known by the bilingual, results indicated that each language learning method successfully created such lexical connections, but these links were weaker in strength than those of the base language that was used during learning. Based on the current results, new models of lexical access are proposed which vary based on the use of language learning methods. The current findings also have strong implications and applications to the field of foreign language acquisition, primarily for bilingual language learners acquiring an L3.
Keywords: Foreign language learning; Lexical organization; Bilinguals; Psychology (0621)